LITERATURE REVIEW: HIV PREVENTION IN WOMEN SEX PRODUCER WITH PHYSICAL DISABILITIES - Sarah Wulan Putrianti; Nurfika Asmaningrum (UPT Penerbitan Universitas Jember, 2023)
Introduction: Many behaviors are carried out by FSW in preventing HIV/AIDS, namely not using condoms, taking antibiotics to prevent HIV disease, washing the vagina with toothpaste, squatting after having sexual intercourse with customers, drinking herbal/special ingredients to clean vital areas. Lack of knowledge and economic factors are one of the factors causing the emergence of HIV/AIDS. Purpose: this study aims to determine HIV/AIDS prevention behavior among female sex workers with physical disabilities. Method: Literature Review with the PRISMA approach. Literature search using electronic database such as PubMed, Google Scholar and Science Direct. Literature review was conducted on international journals published in the last 5 years, available in full text. Results: A total of 3.112.416 articles were identified. Fifteen articles that have been analyzed the results show that the knowledge of FSW about STIs and HIV/AIDS has sufficient knowledge and low education, are in the age range of 26-35 years, but in FSW with disabilities there is still stigma and discrimination and sexual violence, workers with disabilities experience stigma and discrimination in the workplace, online-based education using HIV/AIDS prevention videos for people with speech impairments is effective in increasing the knowledge and attitudes of people with speech impairments in preventing risky behavior, people with disabilities are affected by poverty, which includes lack of access to education, health and income so that women with disabilities are at higher risk of being exposed to HIV. Discussion: The vulnerability of female sex workers with physical disabilities will increase the number of HIV/AIDS cases. The gap between women sex workers and physical disabilities requires advocacy at local and national levels to support health service improvements. Conclusion: persons with disabilities are diverse and their HIV risk varies from individual sexual behavior to contextual factors such as poverty, lack of access to health and education, and experiences of violence.